Gambaran Keterampilan Perkembangan Motorik Kasar pada Anak Toddler (usia 1-3 tahun) di Posyandu Wilayah Kerja Puskesmas Tabanan III - Desak Gede Yenny Apriani; Desak Made Firsia Sastra Putri; I Gede Nyoman Ardi Supartha; Ni Putu Ayu Dina Febriani (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2023)
Background: One important aspect of the development process is gross motor development, namely body movements using large muscles. Gross motor skills are the ability to move various parts of the body that involve the activity of the large muscles on command and regulate body movements against various influences from outside and from within the body. Interviews conducted by researchers with 10 mothers who had children aged 1-3 years found seven mothers who said they did not provide stimulation to their children, such as not inviting their children to play because they had to work, not teaching children how to stand or learn to walk according to the child's age. Purpose: The purpose of this study was to find out the description of gross motor skills in toddlers (1-3 years old) in the Working Area of the Tabanan III Health Center. Methods: This research is a descriptive analytic study using a cross-sectional approach. Respondents were selected based on purposive sampling, namely all mothers who had children aged 1-3 years at the Posyandu, Tabanan III Health Center, as many as 83 people using an observation sheet. Results: This study shows that the description of gross motor skills development in the Posyandu Work Area of the Tabanan III Health Center is in the normal category as many as 57 respondents (68.7%) while those in the abnormal category are as many as 26 respondents (31.3%). It was also found that most of the mothers were >30 years old, most of the mothers had graduate education, and most of the children were male. Conclusion: Gross motor development skills in toddlers (age 1-3 years) in the Posyandu Working Area of the Tabanan III Health Center are in the normal category